Missed opportunities to prevent mother‐to‐child transmission of HIV in Italy. Issue 5 (29th March 2019) - Di Biagio, A; Taramasso, L; Gustinetti, G; Burastero, G; Giacomet, V; La Rovere, D; Genovese, O; Giaquinto, C; Rampon, O; Carloni, I; Hyppolite, TK; Palandri, L; et al.
Abstract : Objectives: Vertical transmission of HIV can be effectively controlled through antenatal screening, antiretroviral treatment and the services provided during and after childbirth for mother and newborn. In Italy, the National Health Service guarantees universal access to prenatal care for all women, including women with HIV infection. Despite this, children are diagnosed with HIV infection every year. The aim of the study was to identify missed opportunities for prevention of mother‐to‐child transmission of HIV. Methods: The Italian Register for HIV Infection in Children, which was started in 1985 and involves 106 hospitals throughout the country, collects data on all new cases of HIV infection in children. For this analysis, we reviewed the database for the period 2005 to 2015. Results: We found 79 HIV‐1‐infected children newly diagnosed after birth in Italy. Thirty‐two of the mothers were Italian. During the pregnancy, only 15 of 19 women with a known HIV diagnosis were treated with antiretroviral treatment, while, of 34 women who had received an HIV diagnosis before labour began, only 23 delivered by caesarean section and 17 received intrapartum prophylaxis. In 25 mothers, HIV infection was diagnosed during pregnancy or in the peripartum period. Thirty‐one newborns received antiretroviral prophylaxis and 39 received infant formula. Conclusions: We found an unacceptable number of missed opportunities to prevent mother‐to‐child transmission (MCTC). Eliminating HIV MTCT is a universal World Health Organization goal. Elucidating organization failures in Italy over the past decade should help to improve early diagnosis and to reach the zero transmission target in newborns.